The γ (c) family of cytokines: fine-tuning signals from IL-2 and IL-21 in the regulation of the immune response - Spolski, Rosanne (F1000Res, 2017)
Interleukin (IL)-2, IL-4, IL-7, IL-9, IL-15, and IL-21 form a family of cytokines based on the sharing of a receptor component, the common cytokine receptor γ chain, γ (c), which is encoded by the gene mutated in humans with X-linked severe combined immunodeficiency (XSCID). Together, these cytokines play critical roles in lymphoid development, differentiation, growth, and survival as well as mediating effector function. Here, we provide an overview of the main actions of members of this cytokine family but then primarily focus on IL-2 and IL-21, discussing their dynamic interplay and contributions to a fine-tuned immune response. Moreover, we discuss the therapeutic utility of modulating their actions, particularly for autoimmunity and cancer.